Recent advances in the abatement of volatile organic compounds (VOCs) and chlorinated-VOCs by non-thermal plasma technology: A review. (December 2022) - Mu, Yibing; Williams, Paul T.
Abstract: Most of the volatile organic compounds (VOCs) and especially the chlorinated volatile organic compounds (Cl–VOCs), are regarded as major pollutants due to their properties of volatility, diffusivity and toxicity which pose a significant threat to human health and the eco-environment. Catalytic degradation of VOCs and Cl–VOCs to harmless products is a promising approach to mitigate the issues caused by VOCs and Cl–VOCs. Non-thermal plasma (NTP) assisted catalysis is a promising technology for the efficient degradation of VOCs and Cl–VOCs with higher selectivity under relatively mild conditions compared with conventional thermal catalysis. This review summarises state-of-the-art research of the in plasma catalysis (IPC) of VOCs degradation from three major aspects including: (i) the design of catalysts, (ii) the strategies of deep catalytic degradation and by-products inhibition, and (iii) the fundamental research into mechanisms of NTP activated catalytic VOCs degradation. Particular attention is also given to Cl–VOCs due to their characteristic properties of higher stability and toxicity. The catalysts used for the degradation Cl–VOCs, chlorinated by-products formation and the degradation mechanism of Cl–VOCs are systematically reviewed in each chapter. Finally, a perspective on future challenges and opportunities in the development of NTP assisted VOCs catalytic degradation were discussed. Graphical abstract: Image 1 Highlights: Catalytic degradation of Cl–VOCs under NTP condition is systematically reviewed. The different catalysts used in NTP for Cl-VOC control are covered. Formation and control strategies of hazardous by-products are reviewed. Techniques used for understanding the degradation mechanisms are reviewed.